2016
DOI: 10.1051/epjconf/201612502004
|View full text |Cite
|
Sign up to set email alerts
|

On Geoneutrinos

Abstract: Abstract. Experimental data on geoneutrinos allow to admit that masses of U, Th and K in the Earth can be up to m U = 1.7 · 10 17 kg, m Th = 6.7 · 10 17 kg and m K /m Earth ∼ 2%. These values correspond to intrinsic Earth heat flux in ∼300 TW. The most part of this flux goes up in rift zones as a heated gases. Argo Project results and the measurements of the Moon intrinsic heat flux support the existence of such a big flux. So large of U, Th, K abundances were predicted by Adjusted Hydridic Earth model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the previous 19th International Seminar on High Energy Physics, Quarks-2016, we discussed the problem of geo-neutrino [3]. In this work we demonstrated that the experimental data on geo-neutrinos allow to admit that masses of U, Th and K in the Earth can be up to m U = 1.7 • 10 17 kg, m T h = 6.7 • 10 17 kgandm K /m Earth ∼ 2%.…”
Section: Introductionmentioning
confidence: 80%
“…In the previous 19th International Seminar on High Energy Physics, Quarks-2016, we discussed the problem of geo-neutrino [3]. In this work we demonstrated that the experimental data on geo-neutrinos allow to admit that masses of U, Th and K in the Earth can be up to m U = 1.7 • 10 17 kg, m T h = 6.7 • 10 17 kgandm K /m Earth ∼ 2%.…”
Section: Introductionmentioning
confidence: 80%